Resin composition

A resin composition with epoxy resin and maleimide compounds ensures high adhesion and low melt viscosity, addressing the adhesion and embedding challenges in printed wiring boards post-HAST tests.

JP7613494B2Active Publication Date: 2025-01-15AJINOMOTO CO INC
View PDF 16 Cites 0 Cited by

Patent Information

Application Number
JP2023035365
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-03-08
Publication Date
2025-01-15
Estimated Expiration
2037-09-06

AI Technical Summary

Technical Problem

Existing resin compositions for printed wiring boards fail to maintain high adhesion between the conductor and insulating layers after a super accelerated high temperature and high humidity life test (HAST test), and lack sufficient wiring embedding properties.

Method used

A resin composition comprising an epoxy resin and a maleimide compound with specific alkyl or alkylene groups, optionally including an active ester compound, inorganic filler, and other additives, which enhances adhesion and reduces melt viscosity.

Benefits of technology

The composition maintains high adhesion to conductor layers after HAST tests, exhibits excellent smear removability, and provides low melt viscosity for improved wiring embedding properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007613494000020
    Figure 0007613494000020
  • Figure 0007613494000001
    Figure 0007613494000001
  • Figure 0007613494000002
    Figure 0007613494000002
Patent Text Reader

Abstract

Provided are a resin composition that can provide an insulating layer that has high adhesion to a conductor layer after a HAST test and has a low melt viscosity; a resin sheet that includes the resin composition; and a printed wiring board and a semiconductor device that include an insulating layer formed using the resin composition. [Solution] A resin composition comprising (A) an epoxy resin and (B) a maleimide compound, wherein component (B) contains at least one of an alkyl group having 5 or more carbon atoms and an alkylene group having 5 or more carbon atoms.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition. The present invention further relates to a resin sheet, a printed wiring board, and a semiconductor device obtained by using the resin composition. [Background technology]

[0002] 2. Description of the Related Art A known manufacturing technique for printed wiring boards is a build-up method in which insulating layers and conductor layers are alternately stacked.

[0003] As an insulating material for a printed wiring board used in such an insulating layer, for example, Patent Document 1 discloses a thermosetting resin composition containing a maleimide compound (A) having a melting point of 40° C. or less, an epoxy compound (B), a cyanate ester compound (C), and an inorganic filler (D). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2016-010964 A Summary of the Invention [Problem to be solved by the invention]

[0005] From the viewpoint of enabling the formation of fine pattern wiring, enhancing mounting reliability of printed wiring boards, and enhancing connection reliability of printed wiring boards, it is desirable for the insulating layer to have high adhesion to the conductor layer. Therefore, in recent years, the performance of the insulating layer has been required to have high adhesion to the conductor layer. Furthermore, in order to enhance the long-term reliability of printed wiring boards, it is desirable for the insulating layer to have high adhesion to the conductor layer even after a highly accelerated high temperature and high humidity life test (HAST test). It is also required to maintain a low melt viscosity and improve wiring embedding properties.

[0006] As described above, Patent Document 1 discloses that maleimide is contained in a resin composition used for the insulating layer of a printed wiring board. However, Patent Document 1 does not consider adhesion and wiring embedding properties after a HAST test. The present inventors have found that the adhesion between a conductor layer and an insulating layer can be maintained even after a HAST test by using a specific maleimide compound in a resin composition. They have also found that the wiring embedding properties are excellent by using a specific maleimide compound in a resin composition. Thus, as far as the present inventors know, the technical idea of ​​obtaining an insulating layer that can maintain high adhesion after a HAST test by including a specific maleimide compound in a resin composition has not been proposed at all.

[0007] The object of the present invention is to provide a resin composition which can obtain an insulating layer having high adhesion to a conductor layer after a HAST test and has a low melt viscosity; a resin sheet containing the resin composition; and a printed wiring board and a semiconductor device having an insulating layer formed using the resin composition. [Means for solving the problem]

[0008] In order to achieve the object of the present invention, the present inventors conducted extensive research and found that, by incorporating a specific maleimide compound, the adhesion between the conductor layer and the insulating layer can be maintained even after the HAST test. Furthermore, they found that in addition to the above adhesion, the smear removal property is excellent and the melt viscosity of the resin composition is low, and thus the present invention was completed.

[0009] That is, the present invention includes the following. [1] A resin composition comprising (A) an epoxy resin and (B) a maleimide compound, A resin composition, in which the component (B) contains at least one of an alkyl group having 5 or more carbon atoms and an alkylene group having 5 or more carbon atoms. [2] The resin composition according to [1], wherein the component (B) is represented by the following general formula (B-1): [ka] In formula (B-1), R each independently represents an alkylene group having 5 or more carbon atoms which may have a substituent, and L represents a single bond or a divalent linking group. [3] The resin composition according to [1] or [2], wherein the content of component (B) is 0.1% by mass or more and 10% by mass or less, when the total amount of non-volatile components in the resin composition is 100% by mass. [4] The resin composition according to any one of [1] to [3], further comprising (C) an active ester compound. [5] The resin composition according to [4], wherein the content of component (C) is 5% by mass or more, relative to 100% by mass of the non-volatile components in the resin composition. [6] The resin composition according to any one of [1] to [5], further comprising (D) an inorganic filler. [7] The resin composition according to [6], wherein the content of component (D) is 50 mass% or more. [8] The resin composition according to any one of [1] to [7], wherein in general formula (B-1), L is an oxygen atom, an arylene group having 6 to 24 carbon atoms which may have a substituent, an alkylene group having 1 to 50 carbon atoms which may have a substituent, an alkyl group having 5 or more carbon atoms, a divalent group derived from phthalimide, a divalent group derived from pyromellitic diimide, or a divalent group consisting of a combination of two or more of these groups. [9] The resin composition according to any one of [1] to [8], wherein the component (B) is represented by the following general formula (B-2): [ka] In formula (B-2), R' each independently represents an alkylene group having 5 or more carbon atoms which may have a substituent, A each independently represents an alkylene group having 5 or more carbon atoms which may have a substituent or a divalent group having an aromatic ring which may have a substituent, and n represents an integer of 1 to 10.

[10] In the general formula (B-2), each A independently represents a cyclic alkylene group having 5 or more carbon atoms which may have a substituent; a divalent group having a benzene ring which may have a substituent; a divalent group having a phthalimide ring which may have a substituent; or a divalent group having a pyromellitic diimide ring which may have a substituent. The resin composition according to [9].

[11] The resin composition according to any one of [1] to

[10] , which is for forming an insulating layer of a printed wiring board.

[12] The resin composition according to any one of [1] to

[11] , which is for forming an interlayer insulating layer of a printed wiring board.

[13] A resin sheet comprising a support and a resin composition layer formed on the support from the resin composition according to any one of [1] to

[12] .

[14] The resin sheet according to

[13] , wherein the resin composition layer has a thickness of 25 μm or less.

[15] A printed wiring board including a first conductor layer, a second conductor layer, and an insulating layer formed between the first conductor layer and the second conductor layer, The printed wiring board, wherein the insulating layer is a cured product of the resin composition according to any one of [1] to

[12] .

[16] A semiconductor device comprising the printed wiring board according to

[15] . Effect of the Invention

[0010] According to the present invention, it is possible to provide a resin composition that can obtain an insulating layer that has high adhesion to a conductor layer after a HAST test and has a low melt viscosity; a resin sheet that includes the resin composition; a printed wiring board that has an insulating layer formed using the resin composition, and a semiconductor device. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 is a partial cross-sectional view that illustrates an example of a printed wiring board. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The resin composition, resin sheet, printed wiring board, and semiconductor device of the present invention will be described in detail below.

[0013] [Resin composition] The resin composition of the present invention comprises (A) an epoxy resin and (B) a maleimide compound, and the component (B) contains at least one of an alkyl group having 5 or more carbon atoms and an alkylene group having 5 or more carbon atoms.

[0014] By incorporating a maleimide compound containing at least one of an alkyl group having 5 or more carbon atoms and an alkylene group having 5 or more carbon atoms into a resin composition, it is possible to obtain a cured product that can maintain adhesion with a conductor layer even after a HAST test and also has excellent smear removal properties. In addition, by incorporating the maleimide compound into a resin composition, it is possible to obtain a resin composition with a low melt viscosity. In addition, a cured product that can maintain high adhesion even after a HAST test can usually exhibit high adhesion for a long period of time.

[0015] In addition to the components (A) and (B), the resin composition may contain, as necessary, an active ester compound (C), an inorganic filler (D), a curing agent (E), a curing accelerator (F), a thermoplastic resin (G), and any additives (H). Each component contained in the resin composition of the present invention will be described in detail below.

[0016] <(A) Epoxy resin> The resin composition includes an epoxy resin (A). Examples of the epoxy resin (A) include bixylenol type epoxy resin, bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol S type epoxy resin, bisphenol AF type epoxy resin, dicyclopentadiene type epoxy resin, trisphenol type epoxy resin, naphthol novolac type epoxy resin, phenol novolac type epoxy resin, tert-butyl-catechol type epoxy resin, naphthalene type epoxy resin, naphthol type epoxy resin, anthracene type epoxy resin, glycidylamine type epoxy resin, glycidyl ester type epoxy resin, cresol novolac type epoxy resin, biphenyl type epoxy resin, linear aliphatic epoxy resin, epoxy resin having a butadiene structure, alicyclic epoxy resin, heterocyclic epoxy resin, spiro ring-containing epoxy resin, cyclohexane type epoxy resin, cyclohexane dimethanol type epoxy resin, naphthylene ether type epoxy resin, trimethylol type epoxy resin, and tetraphenylethane type epoxy resin. The epoxy resins may be used alone or in combination of two or more.

[0017] (A) epoxy resin preferably has two or more epoxy groups in one molecule. When the non-volatile component of the epoxy resin is 100 mass%, it is preferable that at least 50 mass% of the epoxy resin has two or more epoxy groups in one molecule. Among them, the resin composition preferably contains a combination of an epoxy resin that is liquid at a temperature of 20°C (hereinafter also referred to as "liquid epoxy resin") and an epoxy resin that is solid at a temperature of 20°C (hereinafter also referred to as "solid epoxy resin"). As the liquid epoxy resin, a liquid epoxy resin having two or more epoxy groups in one molecule is preferable, and an aromatic liquid epoxy resin having two or more epoxy groups in one molecule is more preferable. As the solid epoxy resin, a solid epoxy resin having three or more epoxy groups in one molecule is preferable, and an aromatic solid epoxy resin having three or more epoxy groups in one molecule is more preferable. In the present invention, an aromatic epoxy resin means an epoxy resin having an aromatic ring in its molecule.

[0018] As the liquid epoxy resin, bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol AF type epoxy resin, naphthalene type epoxy resin, glycidyl ester type epoxy resin, glycidyl amine type epoxy resin, phenol novolac type epoxy resin, alicyclic epoxy resin having an ester skeleton, cyclohexane type epoxy resin, cyclohexane dimethanol type epoxy resin, glycidyl amine type epoxy resin, and epoxy resin having a butadiene structure are preferred, and bisphenol A type epoxy resin and bisphenol F type epoxy resin are more preferred. Specific examples of liquid epoxy resins include "HP4032", "HP4032D", and "HP4032SS" (naphthalene type epoxy resins) manufactured by DIC Corporation, "828US", "jER828EL", "825", "Epikote 828EL" (bisphenol A type epoxy resin), "jER807", "1750" (bisphenol F type epoxy resin), "jER152" (phenol novolac type epoxy resin), "630", and "630LSD" (glycidylamine type epoxy resin) manufactured by Mitsubishi Chemical Corporation, and "ZX1059" (bisphenol A type epoxy resin) manufactured by Nippon Steel & Sumitomo Metal Chemical Co., Ltd. Examples of epoxy resins include "EX-721" (a mixture of bisphenol A type epoxy resin and bisphenol F type epoxy resin) manufactured by Nagase ChemteX Corporation (glycidyl ester type epoxy resin), "Celloxide 2021P" (alicyclic epoxy resin having an ester skeleton) manufactured by Daicel Corporation, "PB-3600" (epoxy resin having a butadiene structure), "ZX1658" and "ZX1658GS" (liquid 1,4-glycidylcyclohexane type epoxy resin) manufactured by Nippon Steel & Sumikin Chemical Co., Ltd., and "630LSD" (glycidylamine type epoxy resin) manufactured by Mitsubishi Chemical Corporation. These may be used alone or in combination of two or more.

[0019] As the solid epoxy resin, bixylenol type epoxy resin, naphthalene type epoxy resin, naphthalene type tetrafunctional epoxy resin, cresol novolac type epoxy resin, dicyclopentadiene type epoxy resin, trisphenol type epoxy resin, naphthol type epoxy resin, biphenyl type epoxy resin, naphthylene ether type epoxy resin, anthracene type epoxy resin, bisphenol A type epoxy resin, bisphenol AF type epoxy resin, and tetraphenylethane type epoxy resin are preferred, and naphthalene type epoxy resin is more preferred. Specific examples of solid epoxy resins include "HP4032H" (naphthalene type epoxy resin), "HP-4700", "HP-4710" (naphthalene type tetrafunctional epoxy resin), "N-690" (cresol novolac type epoxy resin), "N-695" (cresol novolac type epoxy resin), "HP-7200" (dicyclopentadiene type epoxy resin), "HP-7200HH", "HP-7200H", "EXA-7311", "EXA-7311-G3", "EXA-7311-G4", "EXA-7311-G4S", "HP6000" (naphthylene ether type epoxy resin), and "EPPN-502H" (trisphenol type epoxy resin), "NC7000L" (naphthol novolac type epoxy resin), "NC3000H", "NC3000", "N" (manufactured by Nippon Kayaku Co., Ltd.). Examples of epoxy resins include "C3000L" and "NC3100" (biphenyl type epoxy resins), "ESN475V" (naphthalene type epoxy resins) and "ESN485" (naphthol novolac type epoxy resins) manufactured by Nippon Steel & Sumitomo Metal Chemical Co., Ltd., "YX4000H", "YX4000", "YL6121" (biphenyl type epoxy resins), "YX4000HK" (bixylenol type epoxy resins), and "YX8800" (anthracene type epoxy resins) manufactured by Mitsubishi Chemical Corporation, "PG-100" and "CG-500" manufactured by Osaka Gas Chemical Co., Ltd., "YL7760" (bisphenol AF type epoxy resins) and "YL7800" (fluorene type epoxy resins) manufactured by Mitsubishi Chemical Corporation, and "jER1010" (solid bisphenol A type epoxy resins) and "jER1031S" (tetraphenylethane type epoxy resins) manufactured by Mitsubishi Chemical Corporation. These may be used alone or in combination of two or more.

[0020] When a liquid epoxy resin and a solid epoxy resin are used in combination as the (A) component, the ratio of the amounts thereof (liquid epoxy resin: solid epoxy resin) is preferably in the range of 1:1 to 1:20 by mass. By setting the ratio of the liquid epoxy resin to the solid epoxy resin in this range, it is possible to obtain the following effects: i) when used in the form of a resin sheet, appropriate adhesion is obtained; ii) when used in the form of a resin sheet, sufficient flexibility is obtained and handling is improved; and iii) a cured product having sufficient breaking strength can be obtained. From the viewpoint of the above effects i) to iii), the ratio of the liquid epoxy resin to the solid epoxy resin (liquid epoxy resin: solid epoxy resin) is more preferably in the range of 1:1 to 1:15 by mass, and even more preferably in the range of 1:1 to 1:10.

[0021] From the viewpoint of obtaining an insulating layer exhibiting good mechanical strength and insulating reliability, the content of the (A) component in the resin composition is preferably 5% by mass or more, more preferably 10% by mass or more, and even more preferably 15% by mass or more, when the non-volatile components in the resin composition are taken as 100% by mass. The upper limit of the epoxy resin content is not particularly limited as long as the effects of the present invention are exhibited, but is preferably 30% by mass or less, more preferably 25% by mass or less, and even more preferably 20% by mass or less. In the present invention, the content of each component in the resin composition is a value when the non-volatile components in the resin composition are taken as 100 mass %, unless otherwise specified.

[0022] The epoxy equivalent of the (A) component is preferably 50 to 5000, more preferably 50 to 3000, even more preferably 80 to 2000, and even more preferably 110 to 1000. Within this range, the crosslink density of the cured product is sufficient, and an insulating layer with small surface roughness can be obtained. The epoxy equivalent can be measured according to JIS K7236, and is the mass of a resin containing one equivalent of an epoxy group.

[0023] The weight average molecular weight of the component (A) is preferably 100 to 5000, more preferably 250 to 3000, and further preferably 400 to 1500. Here, the weight average molecular weight of the epoxy resin is a polystyrene-equivalent weight average molecular weight measured by gel permeation chromatography (GPC).

[0024] <(B) Maleimide compound> The resin composition contains a maleimide compound containing at least one of an alkyl group having 5 or more carbon atoms and an alkylene group having 5 or more carbon atoms. The maleimide compound (B) is a compound containing a maleimide group represented by the following formula (1) in the molecule.

[0025] [ka]

[0026] (B) Maleimide compound contains at least one of an alkyl group having 5 or more carbon atoms and an alkylene group having 5 or more carbon atoms. In addition, maleimide compounds containing at least one of an alkyl group having 5 or more carbon atoms and an alkylene group having 5 or more carbon atoms have a flexible molecular structure due to the action of the long carbon chain. Therefore, it is possible to achieve a lower minimum melt viscosity than maleimide compounds containing an arylene group as a main component. Furthermore, since the maleimide group is easily dissolved in an alkaline solution, it is usually possible to obtain a cured product with excellent smear removal properties. Since the alkyl group having 5 or more carbon atoms and the alkylene group having 5 or more carbon atoms have a long carbon chain, they are hydrophobic. Therefore, (B) Maleimide compound is not easily deteriorated in a high temperature and high humidity environment, and can suppress delamination accompanied by destruction of the insulating layer even after the HAST test. As a result, it is possible to obtain an insulating layer having high adhesion to the conductor layer after the HAST test.

[0027] The number of carbon atoms of the alkyl group having 5 or more carbon atoms is preferably 6 or more, more preferably 8 or more, preferably 50 or less, more preferably 45 or less, and even more preferably 40 or less. The alkyl group may be linear, branched, or cyclic, and linear is preferred. Examples of such alkyl groups include pentyl, hexyl, heptyl, octyl, nonyl, and decyl groups. The alkyl group having 5 or more carbon atoms may be a substituent of an alkylene group having 5 or more carbon atoms.

[0028] The number of carbon atoms of the alkylene group having 5 or more carbon atoms is preferably 6 or more, more preferably 8 or more, preferably 50 or less, more preferably 45 or less, and even more preferably 40 or less. The alkylene group may be linear, branched, or cyclic, and linear is preferred. Here, the cyclic alkylene group is a concept that includes the case where it is composed of only a cyclic alkylene group and the case where it contains both a linear alkylene group and a cyclic alkylene group. Examples of such alkylene groups include pentylene, hexylene, heptylene, octylene, nonylene, decylene, undecylene, dodecylene, tridecylene, heptadecylene, hexatriacontylene, a group having an octylene-cyclohexylene structure, a group having an octylene-cyclohexylene-octylene structure, and a group having a propylene-cyclohexylene-octylene structure.

[0029] In the (B) maleimide compound, it is preferred that the alkyl group having 5 or more carbon atoms and the alkylene group having 5 or more carbon atoms are directly bonded to the nitrogen atom of the maleimide group. Here, "directly" means that there is no other group between the nitrogen atom of the maleimide group and the alkyl group or alkylene group. This makes it possible to particularly improve the adhesion and minimum melt viscosity after the HAST test.

[0030] (B) From the perspective of obtaining an insulating layer with high adhesion to the conductor layer after the HAST test, the maleimide compound preferably contains both an alkyl group having 5 or more carbon atoms and an alkylene group having 5 or more carbon atoms.

[0031] The alkyl group having 5 or more carbon atoms and the alkylene group having 5 or more carbon atoms may be bonded to each other to form a ring, and the ring structure includes a spiro ring and a condensed ring. Examples of the ring formed by bonding to each other include a cyclohexane ring and the like.

[0032] The alkyl group having 5 or more carbon atoms and the alkylene group having 5 or more carbon atoms preferably do not have a substituent, but may have a substituent. The substituent is not particularly limited. For example, a halogen atom, -OH, -O-C 1-6 alkyl group, -N(C 1-10 alkyl group) 2 , C 1-10 alkyl group, C 6-10 aryl group, -NH 2 , -CN, -C(O)O-C 1-10 alkyl group, -COOH, -C(O)H, -NO 2 and the like. Here, the term "C p-q " (p and q are positive integers and satisfy p < q) represents that the carbon atom number of the organic group described immediately after this term is p to q. For example, the expression "C 1-10 alkyl group" indicates an alkyl group having 1 to 10 carbon atoms. These substituents may be bonded to each other to form a ring, and the ring structure includes a spiro ring and a condensed ring.

[0033] The above-mentioned substituents may further have a substituent (hereinafter sometimes referred to as a "secondary substituent"). Unless otherwise specified, the same substituents as the above-mentioned substituents may be used as the secondary substituents.

[0034] The number of maleimide groups per molecule of the (B) maleimide compound may be 1, but is preferably 2 or more, and is preferably 10 or less, more preferably 6 or less, and particularly preferably 3 or less. By using the (B) maleimide compound having 2 or more maleimide groups per molecule, it is possible to obtain an insulating layer that has higher adhesion to a conductor layer after HAST testing.

[0035] The (B) maleimide compound may be used alone or in combination of two or more kinds.

[0036] The (B) maleimide compound may contain at least one of an alkyl group having 5 or more carbon atoms and an alkylene group having 5 or more carbon atoms. From the viewpoint of obtaining an insulating layer having higher adhesion to a conductor layer after a HAST test, the maleimide compound is preferably represented by the following general formula (B-1): [ka] In formula (B-1), R each independently represents an alkylene group having 5 or more carbon atoms which may have a substituent, and L represents a single bond or a divalent linking group.

[0037] Each R independently represents an alkylene group having 5 or more carbon atoms which may have a substituent. R has the same meaning as the alkylene group having 5 or more carbon atoms described above, and the preferred range is also the same.

[0038] L represents a single bond or a divalent linking group. Examples of the divalent linking group include an alkylene group, an alkenylene group, an alkynylene group, an arylene group, -C(=O)-, -C(=O)-O-, -NR 0 -(R 0 is a hydrogen atom, an alkyl group having 1 to 3 carbon atoms, an oxygen atom, a sulfur atom, or C(=O)NR 0-, a divalent group derived from phthalimide, a divalent group derived from pyromellitic diimide, and a divalent group consisting of a combination of two or more of these groups. The divalent group derived from phthalimide means a divalent group derived from phthalimide, specifically a group represented by general formula (2). The divalent group derived from pyromellitic diimide means a divalent group derived from pyromellitic diimide, specifically a group represented by general formula (3). In the formula, "*" represents a bond. [ka]

[0039] The alkylene group is preferably an alkylene group having 1 to 50 carbon atoms, more preferably an alkylene group having 1 to 45 carbon atoms, and particularly preferably an alkylene group having 1 to 40 carbon atoms. The alkylene group may be linear, branched, or cyclic. Examples of such alkylene groups include a methylethylene group, a cyclohexylene group, a pentylene group, a hexylene group, a heptylene group, an octylene group, a nonylene group, a decylene group, an undecylene group, a dodecylene group, a tridecylene group, a heptadecylene group, a hexatriacontylene group, a group having an octylene-cyclohexylene structure, a group having an octylene-cyclohexylene-octylene structure, and a group having a propylene-cyclohexylene-octylene structure.

[0040] The alkenylene group is preferably an alkenylene group having 2 to 20 carbon atoms, more preferably an alkenylene group having 2 to 15 carbon atoms, and particularly preferably an alkenylene group having 2 to 10 carbon atoms. This alkenylene group may be linear, branched, or cyclic. Examples of such alkenylene groups include a methylethylenylene group, a cyclohexenylene group, a pentenylene group, a hexenylene group, a heptenylene group, and an octenylene group.

[0041] The alkynylene group is preferably an alkynylene group having 2 to 20 carbon atoms, more preferably an alkynylene group having 2 to 15 carbon atoms, and particularly preferably an alkynylene group having 2 to 10 carbon atoms. The alkynylene group may be linear, branched, or cyclic. Examples of such alkynylene groups include a methylethynylene group, a cyclohexynylene group, a pentynylene group, a hexynylene group, a heptynylene group, and an octynylene group.

[0042] The arylene group is preferably an arylene group having 6 to 24 carbon atoms, more preferably an arylene group having 6 to 18 carbon atoms, still more preferably an arylene group having 6 to 14 carbon atoms, and even more preferably an arylene group having 6 to 10 carbon atoms. Examples of the arylene group include a phenylene group, a naphthylene group, and an anthracenylene group.

[0043] The divalent linking groups, that is, the alkylene group, the alkenylene group, the alkynylene group, and the arylene group, may have a substituent. The substituent is the same as the substituent that may be possessed by the alkyl group having 5 or more carbon atoms represented by R in the general formula (B-1), and is preferably an alkyl group having 5 or more carbon atoms.

[0044] Examples of the divalent group consisting of a combination of two or more of these groups include a divalent group consisting of a combination of an alkylene group, a divalent group derived from phthalimide, and an oxygen atom; a divalent group consisting of a combination of a divalent group derived from phthalimide, an oxygen atom, an arylene group, and an alkylene group; a divalent group consisting of a combination of an alkylene group and a divalent group derived from pyromellitic diimide; and the like. The divalent group consisting of a combination of two or more of these groups may form a ring such as a condensed ring by the combination of each group. In addition, the divalent group consisting of a combination of two or more of these groups may be a repeating unit having a repeating unit number of 1 to 10.

[0045] Among them, L in the general formula (B-1) is preferably an oxygen atom, an arylene group having 6 to 24 carbon atoms which may have a substituent, an alkylene group having 1 to 50 carbon atoms which may have a substituent, an alkyl group having 5 or more carbon atoms, a divalent group derived from phthalimide, a divalent group derived from pyromellitic diimide, or a divalent group consisting of a combination of two or more of these groups. Among them, L is more preferably an alkylene group; a divalent group having a structure of an alkylene group-a divalent group derived from phthalimide-oxygen atom-a divalent group derived from phthalimide; a divalent group having a structure of an alkylene group-a divalent group derived from phthalimide-oxygen atom-arylene group-alkylene group-arylene group-oxygen atom-a divalent group derived from phthalimide; or a divalent group having a structure of an alkylene-a divalent group derived from pyromellitic diimide.

[0046] The maleimide compound represented by general formula (B-1) is preferably represented by general formula (B-2). [ka] In formula (B-2), R' each independently represents an alkylene group having 5 or more carbon atoms which may have a substituent, A each independently represents an alkylene group having 5 or more carbon atoms which may have a substituent or a divalent group having an aromatic ring which may have a substituent, and n represents an integer of 1 to 10.

[0047] Each R' independently represents an alkylene group having 5 or more carbon atoms which may have a substituent. R' is the same as R in general formula (B-1).

[0048] Each A independently represents an alkylene group having 5 or more carbon atoms which may have a substituent, or a divalent group having an aromatic ring which may have a substituent. However, when A represents an alkylene group, the case where it is composed only of a linear alkylene group is excluded. When A represents an alkylene group, it may be either branched or cyclic, and among them, a cyclic alkylene group having 5 or more carbon atoms which may have a substituent is preferred. The number of carbon atoms is preferably 6 or more, more preferably 8 or more, preferably 50 or less, more preferably 45 or less, and even more preferably 40 or less. Examples of such alkylene groups include a group having an octylene-cyclohexylene structure, a group having an octylene-cyclohexylene-octylene structure, and a group having a propylene-cyclohexylene-octylene structure.

[0049] Examples of the aromatic ring in the divalent group having an aromatic ring which may have a substituent include a benzene ring, a naphthalene ring, an anthracene ring, a phthalimide ring, a pyromellitic diimide ring, and an aromatic heterocycle, and the like are mentioned, with a benzene ring, a phthalimide ring, and a pyromellitic diimide ring being preferred. That is, examples of the divalent group having an aromatic ring include a divalent group having a benzene ring which may have a substituent, a divalent group having a phthalimide ring which may have a substituent, and a divalent group having a pyromellitic diimide ring which may have a substituent. Examples of the divalent group having an aromatic ring include a group consisting of a combination of a divalent group derived from phthalimide and an oxygen atom; a group consisting of a combination of a divalent group derived from phthalimide, an oxygen atom, an arylene group, and an alkylene group; a group consisting of a combination of an alkylene group and a divalent group derived from pyromellitic diimide; a divalent group derived from pyromellitic diimide; a group consisting of a combination of a divalent group derived from phthalimide and an alkylene group; and the like. The arylene group and alkylene group are the same as the arylene group and alkylene group in the divalent linking group represented by L in general formula (B-1), and the preferred ranges are also the same.

[0050] The alkylene group and the divalent group having an aromatic ring represented by A may have a substituent. The substituent is the same as the substituent that may be possessed by the alkyl group having 5 or more carbon atoms represented by R in the general formula (B-1).

[0051] Specific examples of the group represented by A include the following groups: In the formula, "*" represents a bond. [ka] [ka]

[0052] The maleimide compound represented by general formula (B-1) is preferably any one of a maleimide compound represented by general formula (B-3) and a maleimide compound represented by general formula (B-4). [ka] In general formula (B-3), R 1 each independently represents an alkylene group having 5 or more carbon atoms which may have a substituent; R 2 each independently represents an oxygen atom, an arylene group, an alkylene group, or a divalent group consisting of a combination of two or more of these groups. n1 represents an integer of 1 to 15. In general formula (B-4), R 3 each independently represents an alkylene group having 5 or more carbon atoms which may have a substituent; R 4 each independently represents a divalent group having an aromatic ring which may have a substituent; R 5 each independently represents an alkyl group having 5 or more carbon atoms. n2 represents an integer of 0 to 10, and each m independently represents an integer of 0 to 4.

[0053] R 1 R each independently represents an alkylene group having 5 or more carbon atoms which may have a substituent. 1is the same as the alkylene group having 5 or more carbon atoms represented by R in general formula (B-1), and is preferably a hexatriacontylene group.

[0054] R 2 R each independently represents an oxygen atom, an arylene group, an alkylene group, or a divalent group consisting of a combination of two or more of these groups. The arylene group and the alkylene group are the same as the arylene group and the alkylene group in the divalent linking group represented by L in the general formula (B-1), and the preferred ranges are also the same. 2 is preferably a divalent group formed by a combination of two or more of these groups, or an oxygen atom.

[0055] Divalent groups formed by combining two or more of these groups include combinations of oxygen atoms, arylene groups, and alkylene groups. Specific examples of divalent groups formed by combining two or more of these groups include the following groups. In the formula, "*" represents a bond. [ka]

[0056] R 3 R each independently represents an alkylene group having 5 or more carbon atoms which may have a substituent. 3 is the same as the alkylene group having 5 or more carbon atoms represented by R in general formula (B-1), and is preferably a hexylene group, a heptylene group, an octylene group, a nonylene group, or a decylene group, more preferably an octylene group.

[0057] R 4 R each independently represents a divalent group having an aromatic ring which may have a substituent. 4is the same as the divalent group having an aromatic ring represented by A in general formula (B-2), and is preferably a group consisting of a combination of an alkylene group and a divalent group derived from pyromellitic diimide; a group consisting of a combination of a divalent group derived from phthalimide and an alkylene group, and more preferably a group consisting of a combination of an alkylene group and a divalent group derived from pyromellitic diimide. The arylene group and alkylene group are the same as the arylene group and alkylene group in the divalent linking group represented by L in general formula (B-1), and the preferred range is also the same.

[0058] R 4 Specific examples of the group represented by the formula include the following groups: In the formula, "*" represents a bond. [ka]

[0059] R 5 R each independently represents an alkyl group having 5 or more carbon atoms. 5 is the same as the above-mentioned alkyl group having 5 or more carbon atoms, and is preferably a hexyl group, a heptyl group, an octyl group, a nonyl group, or a decyl group, more preferably a hexyl group or an octyl group.

[0060] m represents an integer of 0 to 4, preferably an integer of 1 to 3, and more preferably 2.

[0061] Specific examples of the (B) maleimide compound include the following compounds (4) to (7). However, the (B) maleimide compound is not limited to these specific examples. In the formula, n represents an integer of 1 to 10. [ka] [ka]

[0062] Specific examples of the (B) maleimide compound include "BMI1500" (compound of formula (4)), "BMI1700" (compound of formula (5)), "BMI3000J" (compound of formula (6)), and "BMI689" (compound of formula (7)), all manufactured by Designer Molecules.

[0063] The molecular weight of the (B) maleimide compound is preferably 200 or more, more preferably 300 or more, and even more preferably 400 or more, from the viewpoint of improving adhesion to the conductor layer after the HAST test, and is preferably 100,000 or less, more preferably 80,000 or less, and even more preferably 60,000 or less.

[0064] The content of the (B) maleimide compound is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, and more preferably 1% by mass or more, based on 100% by mass of the non-volatile components in the resin composition. The upper limit is preferably 10% by mass or less, more preferably 8% by mass or less, and even more preferably 5% by mass or less or 3% by mass or less. By setting the content of the (B) component within this range, it is possible to further suppress an increase in the minimum melt viscosity of the resin composition, and to obtain a cured product that is more excellent in adhesion between the insulating layer and the conductor layer and in smear removability after the HAST test.

[0065] <(C) Active ester compound> In one embodiment, the resin composition may contain (C) an active ester compound. It is known that the use of an active ester compound usually results in poor smear removability. However, since the resin composition of the present invention contains (B) a maleimide compound, the cured product of the resin composition has excellent smear removability. Therefore, the use of an active ester compound does not result in poor smear removability.

[0066] The active ester compound is not particularly limited, but generally, compounds having two or more highly reactive ester groups in one molecule, such as phenol esters, thiophenol esters, N-hydroxyamine esters, and esters of heterocyclic hydroxy compounds, are preferably used. The active ester compound is preferably one obtained by a condensation reaction between a carboxylic acid compound and / or a thiocarboxylic acid compound and a hydroxy compound and / or a thiol compound. In particular, from the viewpoint of improving heat resistance, an active ester compound obtained from a carboxylic acid compound and a hydroxy compound is preferred, and an active ester compound obtained from a carboxylic acid compound and a phenol compound and / or a naphthol compound is more preferred. Examples of the carboxylic acid compound include benzoic acid, acetic acid, succinic acid, maleic acid, itaconic acid, phthalic acid, isophthalic acid, terephthalic acid, and pyromellitic acid. Examples of phenol compounds or naphthol compounds include hydroquinone, resorcin, bisphenol A, bisphenol F, bisphenol S, phenolphthaline, methylated bisphenol A, methylated bisphenol F, methylated bisphenol S, phenol, o-cresol, m-cresol, p-cresol, catechol, α-naphthol, β-naphthol, 1,5-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 2,6-dihydroxynaphthalene, dihydroxybenzophenone, trihydroxybenzophenone, tetrahydroxybenzophenone, phloroglucin, benzenetriol, dicyclopentadiene-type diphenol compounds, phenol novolac, etc. Here, the term "dicyclopentadiene-type diphenol compounds" refers to diphenol compounds obtained by condensing one molecule of dicyclopentadiene with two molecules of phenol.

[0067] Specifically, active ester compounds containing a dicyclopentadiene-type diphenol structure, active ester compounds containing a naphthalene structure, active ester compounds containing an acetylated product of phenol novolac, and active ester compounds containing a benzoylated product of phenol novolac are preferred, and among these, active ester compounds containing a naphthalene structure and active ester compounds containing a dicyclopentadiene-type diphenol structure are more preferred. The "dicyclopentadiene-type diphenol structure" refers to a divalent structural unit consisting of phenylene-dicyclopentylene-phenylene.

[0068] Commercially available active ester compounds include "EXB9451", "EXB9460", "EXB9460S", "HPC-8000-65T", "HPC-8000H-65TM", "EXB-8000L-65TM", and "EXB-8150-65T" (manufactured by DIC Corporation) as active ester compounds containing a dicyclopentadiene-type diphenol structure, "EXB9416-70BK" (manufactured by DIC Corporation) as an active ester compound containing a naphthalene structure, and "EXB9420-160BK" (manufactured by DIC Corporation) as an active ester compound containing an acetylated product of phenol novolac. Examples of active ester compounds that contain a benzoyl derivative of phenol novolac include "DC808" (manufactured by Mitsubishi Chemical Corporation), "YLH1026" (manufactured by Mitsubishi Chemical Corporation) as an active ester compound that is an acetylated derivative of phenol novolac include "DC808" (manufactured by Mitsubishi Chemical Corporation), and examples of active ester-based curing agents that are benzoyl derivatives of phenol novolac include "YLH1026" (manufactured by Mitsubishi Chemical Corporation), "YLH1030" (manufactured by Mitsubishi Chemical Corporation), and "YLH1048" (manufactured by Mitsubishi Chemical Corporation).

[0069] When the resin composition contains (C) an active ester compound, the ratio of the amount of the epoxy resin to the active ester compound is preferably in the range of 1:0.01 to 1:5, more preferably 1:0.05 to 1:3, and even more preferably 1:0.1 to 1:1.5, in terms of the ratio of [total number of epoxy groups in the epoxy resin]:[total number of reactive groups in the active ester compound]. Here, the reactive group of the active ester compound is an active ester group. The total number of epoxy groups in the epoxy resin is the value obtained by dividing the solid content mass of each epoxy resin by the epoxy equivalent, and the total number of reactive groups in the active ester compound is the value obtained by dividing the solid content mass of each active ester compound by the reactive group ...

[0070] When the resin composition contains the active ester compound (C), the content of the component (C) is preferably 1% by mass or more, more preferably 3% by mass or more, and even more preferably 5% by mass or more, based on 100% by mass of the non-volatile components in the resin composition. The upper limit is preferably 30% by mass or less, more preferably 20% by mass or less, and even more preferably 15% by mass or less. By keeping the content of the component (C) within this range, the peel strength before and after the HAST test can be improved.

[0071] <(D) Inorganic filler> In one embodiment, the resin composition may contain (D) an inorganic filler. The material of (D) the inorganic filler is not particularly limited as long as it is an inorganic compound, but examples thereof include silica, alumina, glass, cordierite, silicon oxide, barium sulfate, barium carbonate, talc, clay, mica powder, zinc oxide, hydrotalcite, boehmite, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, magnesium oxide, boron nitride, aluminum nitride, manganese nitride, aluminum borate, strontium carbonate, strontium titanate, calcium titanate, magnesium titanate, bismuth titanate, titanium oxide, zirconium oxide, barium titanate, barium zirconate titanate, barium zirconate, calcium zirconate, zirconium phosphate, and zirconium tungstate phosphate. Among these, silica is particularly suitable. Examples of silica include amorphous silica, fused silica, crystalline silica, synthetic silica, and hollow silica. In addition, spherical silica is preferable as the silica. The inorganic fillers may be used alone or in combination of two or more.

[0072] (D) Commercially available inorganic fillers include, for example, "SP60-05" and "SP507-05" manufactured by Nippon Steel & Sumitomo Metal Materials Co., Ltd.; "YC100C", "YA050C", "YA050C-MJE", and "YA010C" manufactured by Admatechs Co., Ltd.; "UFP-30" manufactured by Denka Company, Ltd.; "Silfill NSS-3N", "Silfill NSS-4N", and "Silfill NSS-5N" manufactured by Tokuyama Corporation; and "SC2500SQ", "SO-C4", "SO-C2", and "SO-C1" manufactured by Admatechs Co., Ltd.

[0073] Usually, the inorganic filler (D) is contained in the resin composition in the form of particles. From the viewpoint of remarkably obtaining the desired effect of the present invention, the average particle size of the inorganic filler (D) is preferably 0.01 μm or more, more preferably 0.05 μm or more, particularly preferably 0.1 μm or more, and is preferably 5.0 μm or less, more preferably 2.0 μm or less, and even more preferably 1.0 μm or less. In addition, by having the average particle size of the inorganic filler (D) within the above range, it is usually possible to improve the circuit embedding property of the resin composition layer and reduce the surface roughness of the insulating layer.

[0074] The average particle size of the (D) inorganic filler can be measured by a laser diffraction / scattering method based on the Mie scattering theory. Specifically, a particle size distribution of the (D) inorganic filler is created on a volume basis using a laser diffraction / scattering type particle size distribution measuring device, and the median diameter is taken as the average particle size. The measurement sample is preferably one in which the (D) inorganic filler is dispersed in methyl ethyl ketone using ultrasonic waves. Examples of the laser diffraction / scattering type particle size distribution measuring device that can be used include the "LA-500" manufactured by Horiba, Ltd. and the "SALD-2200" manufactured by Shimadzu Corporation.

[0075] The (D) inorganic filler may be surface-treated with a surface treatment agent in order to improve moisture resistance and dispersibility. Examples of the surface treatment agent include aminosilane coupling agents, epoxysilane coupling agents, mercaptosilane coupling agents, silane coupling agents, alkoxysilanes, organosilazane compounds, and titanate coupling agents. Examples of commercially available surface treatment agents include Shin-Etsu Chemical Co., Ltd.'s "KBM403" (3-glycidoxypropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBM803" (3-mercaptopropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBE903" (3-aminopropyltriethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBM573" (N-phenyl-3-aminopropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "SZ-31" (hexamethyldisilazane), Shin-Etsu Chemical Co., Ltd.'s "KBM103" (phenyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBM-4803" (long-chain epoxy-type silane coupling agent), Shin-Etsu Chemical Co., Ltd.'s "KBM-7103" (3,3,3-trifluoropropyltrimethoxysilane), etc. Surface treatment agents may be used alone or in combination of two or more.

[0076] The degree of surface treatment with the surface treatment agent can be evaluated by the amount of carbon per unit surface area of ​​the (D) inorganic filler. From the viewpoint of improving the dispersibility of the (D) inorganic filler, the amount of carbon per unit surface area of ​​the (D) inorganic filler is set to 0.02 mg / m 2 More than 0.1 mg / m is preferable. 2 More preferably, 0.2 mg / m or more 2 On the other hand, from the viewpoint of suppressing an increase in the melt viscosity of the resin varnish and the melt viscosity in the form of a sheet, it is more preferable that the content is 1 mg / m 2 Less than 0.8 mg / m is preferred. 2 Less than 0.5 mg / m is more preferable. 2 The following is even more preferred:

[0077] The carbon amount per unit surface area of ​​the (D) inorganic filler can be measured after the surface-treated (D) inorganic filler is washed with a solvent (e.g., methyl ethyl ketone (MEK)). Specifically, a sufficient amount of MEK as a solvent is added to the (D) inorganic filler that has been surface-treated with a surface treatment agent, and ultrasonic cleaning is performed at 25°C for 5 minutes. After removing the supernatant and drying the solid content, the carbon amount per unit surface area of ​​the (D) inorganic filler can be measured using a carbon analyzer. The carbon analyzer that can be used is the "EMIA-320V" manufactured by Horiba, Ltd.

[0078] From the viewpoint of reducing the thermal expansion coefficient, the content of the (D) inorganic filler is preferably 50% by mass or more, more preferably 55% by mass or more, even more preferably 60% by mass or more or 65% by mass or more, when the non-volatile components in the resin composition are 100% by mass. The upper limit is preferably 85% by mass or less, more preferably 80% by mass or less, even more preferably 75% by mass or less. It is known that the adhesion strength decreases when a large amount of the (D) inorganic filler is blended, but in the present invention, the decrease in adhesion strength can be effectively suppressed even when a large amount of the (D) inorganic filler is blended.

[0079] <(E) Hardener> In one embodiment, the resin composition may contain a (E) curing agent. However, the (C) active ester compound is not included in the (E) curing agent. The (E) curing agent is not particularly limited as long as it has the function of curing the (A) component, and examples thereof include phenol-based curing agents, naphthol-based curing agents, benzoxazine-based curing agents, cyanate ester-based curing agents, and carbodiimide-based curing agents. Among them, from the viewpoint of improving insulation reliability, the (E) curing agent is preferably one or more of phenol-based curing agents, naphthol-based curing agents, cyanate ester-based curing agents, and carbodiimide-based curing agents, and more preferably contains a phenol-based curing agent. The curing agents may be used alone or in combination of two or more.

[0080] As the phenol-based curing agent and naphthol-based curing agent, from the viewpoint of heat resistance and water resistance, a phenol-based curing agent having a novolac structure or a naphthol-based curing agent having a novolac structure is preferable. Also, from the viewpoint of adhesion to the conductor layer, a nitrogen-containing phenol-based curing agent is preferable, and a triazine skeleton-containing phenol-based curing agent is more preferable.

[0081] Specific examples of phenol-based curing agents and naphthol-based curing agents include, for example, "MEH-7700", "MEH-7810", and "MEH-7851" manufactured by Meiwa Kasei Co., Ltd., "NHN", "CBN", and "GPH" manufactured by Nippon Kayaku Co., Ltd., "SN170", "SN180", "SN190", "SN475", "SN485", "SN495", "SN-495V", "SN375", and "SN395" manufactured by Nippon Steel & Sumikin Chemical Co., Ltd., and "TD-2090", "LA-7052", "LA-7054", "LA-1356", "LA-3018-50P", and "EXB-9500" manufactured by DIC Corporation.

[0082] Specific examples of benzoxazine-based curing agents include "HFB2006M" manufactured by Showa Polymer Co., Ltd., and "Pd" and "Fa" manufactured by Shikoku Chemical Industry Co., Ltd.

[0083] Examples of the cyanate ester curing agent include bifunctional cyanate resins such as bisphenol A dicyanate, polyphenol cyanate, oligo(3-methylene-1,5-phenylene cyanate), 4,4'-methylenebis(2,6-dimethylphenyl cyanate), 4,4'-ethylidene diphenyl dicyanate, hexafluorobisphenol A dicyanate, 2,2-bis(4-cyanate)phenylpropane, 1,1-bis(4-cyanate phenylmethane), bis(4-cyanate-3,5-dimethylphenyl)methane, 1,3-bis(4-cyanate phenyl-1-(methylethylidene))benzene, bis(4-cyanate phenyl)thioether, and bis(4-cyanate phenyl)ether; polyfunctional cyanate resins derived from phenol novolac and cresol novolac; and prepolymers in which these cyanate resins are partially converted to triazine. Specific examples of cyanate ester-based curing agents include "PT30" and "PT60" (phenol novolac type multifunctional cyanate ester resins), "ULL-950S" (multifunctional cyanate ester resin), "BA230", and "BA230S75" (prepolymers in which part or all of bisphenol A dicyanate has been converted to triazine to form a trimer), all of which are manufactured by Lonza Japan.

[0084] Specific examples of carbodiimide-based curing agents include "V-03" and "V-07" manufactured by Nisshinbo Chemical Inc.

[0085] When the resin composition contains a curing agent (E), the ratio of the amount of the epoxy resin to the curing agent is preferably in the range of 1:0.01 to 1:2, more preferably 1:0.01 to 1:3, and even more preferably 1:0.01 to 1:1.5, in terms of the ratio of [total number of epoxy groups in the epoxy resin]:[total number of reactive groups in the curing agent]. Here, the reactive group in the curing agent is an active hydroxyl group or the like, and varies depending on the type of the curing agent. The total number of epoxy groups in the epoxy resin is the value obtained by dividing the solid content mass of each epoxy resin by the epoxy equivalent, and the total number of reactive groups in the curing agent is the value obtained by dividing the solid content mass of each curing agent by the reactive group ...

[0086] When the resin composition contains the (C) active ester compound and the (E) curing agent, the ratio of the amount of the epoxy resin to the active ester compound, expressed as the ratio of [total number of epoxy groups in the epoxy resin]:[total number of reactive groups in the (C) and (E) components], is preferably in the range of 1:0.01 to 1:5, more preferably 1:0.01 to 1:3, and even more preferably 1:0.01 to 1:1.5. By setting the ratio of the amount of the epoxy resin to the (C) and (E) components in this range, the heat resistance of the cured product of the resin composition is further improved.

[0087] When the resin composition contains a (E) curing agent, the content of the (E) curing agent is preferably 0.1% by mass or more, more preferably 0.3% by mass or more, and more preferably 0.5% by mass or more, based on 100% by mass of the non-volatile components in the resin composition. The upper limit is preferably 5% by mass or less, more preferably 3% by mass or less, and even more preferably 1% by mass or less. By setting the content of the (E) curing agent within this range, the adhesion to the conductor layer after the HAST test can be improved.

[0088] <(F) Curing accelerator> In one embodiment, the resin composition may contain (F) a curing accelerator. Examples of the curing accelerator include phosphorus-based curing accelerators, amine-based curing accelerators, imidazole-based curing accelerators, guanidine-based curing accelerators, and metal-based curing accelerators. Phosphorus-based curing accelerators, amine-based curing accelerators, imidazole-based curing accelerators, and metal-based curing accelerators are preferred, and amine-based curing accelerators are more preferred. The curing accelerator may be used alone or in combination of two or more.

[0089] Examples of the phosphorus-based curing accelerator include triphenylphosphine, phosphonium borate compounds, tetraphenylphosphonium tetraphenylborate, n-butylphosphonium tetraphenylborate, tetrabutylphosphonium decanoate, (4-methylphenyl)triphenylphosphonium thiocyanate, tetraphenylphosphonium thiocyanate, butyltriphenylphosphonium thiocyanate, and the like, with triphenylphosphine and tetrabutylphosphonium decanoate being preferred.

[0090] Examples of the amine curing accelerator include trialkylamines such as triethylamine and tributylamine, 4-dimethylaminopyridine, benzyldimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, and 1,8-diazabicyclo(5,4,0)-undecene, with 4-dimethylaminopyridine and 1,8-diazabicyclo(5,4,0)-undecene being preferred.

[0091] Examples of the imidazole curing accelerator include 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazolium trimellitate, 1-cyanoethyl-2-phenylimidazolium trimellitate, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine, 2, 4-Diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid adduct, 2-phenylimidazole isocyanuric acid adduct, 2-phenyl-4,5-dihydroxymethylimidazole, 2-furan Examples of the imidazole compounds include imidazole compounds such as 2-ethyl-4-methyl-5-hydroxymethylimidazole, 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole, 1-dodecyl-2-methyl-3-benzylimidazolium chloride, 2-methylimidazoline, and 2-phenylimidazoline, as well as adducts of imidazole compounds and epoxy resins. Of these, 2-ethyl-4-methylimidazole and 1-benzyl-2-phenylimidazole are preferred.

[0092] As the imidazole-based curing accelerator, a commercially available product may be used, for example, "P200-H50" manufactured by Mitsubishi Chemical Corporation.

[0093] Examples of the guanidine curing accelerator include dicyandiamide, 1-methylguanidine, 1-ethylguanidine, 1-cyclohexylguanidine, 1-phenylguanidine, 1-(o-tolyl)guanidine, dimethylguanidine, diphenylguanidine, trimethylguanidine, tetramethylguanidine, pentamethylguanidine, 1,5,7-triazabicyclo[4.4.0]dec-5-ene, and 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene. Examples of such biguanide include o-[4.4.0]dec-5-ene, 1-methylbiguanide, 1-ethylbiguanide, 1-n-butylbiguanide, 1-n-octadecylbiguanide, 1,1-dimethylbiguanide, 1,1-diethylbiguanide, 1-cyclohexylbiguanide, 1-allylbiguanide, 1-phenylbiguanide, and 1-(o-tolyl)biguanide. Of these, dicyandiamide and 1,5,7-triazabicyclo[4.4.0]dec-5-ene are preferred.

[0094] Examples of metal-based curing accelerators include organometallic complexes or organometallic salts of metals such as cobalt, copper, zinc, iron, nickel, manganese, and tin. Specific examples of organometallic complexes include organocobalt complexes such as cobalt(II) acetylacetonate and cobalt(III) acetylacetonate, organocopper complexes such as copper(II) acetylacetonate, organozinc complexes such as zinc(II) acetylacetonate, organoiron complexes such as iron(III) acetylacetonate, organonickel complexes such as nickel(II) acetylacetonate, and organomanganese complexes such as manganese(II) acetylacetonate. Examples of organometallic salts include zinc octylate, tin octylate, zinc naphthenate, cobalt naphthenate, tin stearate, and zinc stearate.

[0095] When the resin composition contains (F) a curing accelerator, the content of the curing accelerator is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, and even more preferably 0.1% by mass or more, based on 100% by mass of the non-volatile components in the resin composition. The upper limit is preferably 3% by mass or less, more preferably 2% by mass or less, and even more preferably 1% by mass or less. By setting the content of the curing accelerator within this range, even if an inorganic filler with a small average particle size is used, a cured product with excellent adhesion after HAST test can be obtained.

[0096] <(G)Thermoplastic resin> In one embodiment, the resin composition may contain (G) thermoplastic resin. (G) Thermoplastic resins include, for example, phenoxy resins, polyvinyl acetal resins, polyolefin resins, polybutadiene resins, polyimide resins, polyamideimide resins, polyetherimide resins, polysulfone resins, polyethersulfone resins, polyphenylene ether resins, polycarbonate resins, polyetheretherketone resins, polyester resins, etc., and phenoxy resins are preferred. The thermoplastic resins may be used alone or in combination of two or more.

[0097] The polystyrene-equivalent weight average molecular weight of the (G) thermoplastic resin is preferably 38,000 or more, more preferably 40,000 or more, and even more preferably 42,000 or more. The upper limit is preferably 100,000 or less, more preferably 70,000 or less, and even more preferably 60,000 or less. The polystyrene-equivalent weight average molecular weight of the (G) thermoplastic resin is measured by gel permeation chromatography (GPC). Specifically, the polystyrene-equivalent weight average molecular weight of the (G) thermoplastic resin is measured at a column temperature of 40° C. using a measuring device LC-9A / RID-6A manufactured by Shimadzu Corporation, a column Shodex K-800P / K-804L / K-804L manufactured by Showa Denko K.K., chloroform or the like as a mobile phase, and can be calculated using a calibration curve of standard polystyrene.

[0098] Examples of the phenoxy resin include phenoxy resins having one or more skeletons selected from the group consisting of bisphenol A skeleton, bisphenol F skeleton, bisphenol S skeleton, bisphenolacetophenone skeleton, novolac skeleton, biphenyl skeleton, fluorene skeleton, dicyclopentadiene skeleton, norbornene skeleton, naphthalene skeleton, anthracene skeleton, adamantane skeleton, terpene skeleton, and trimethylcyclohexane skeleton. The terminal of the phenoxy resin may be any functional group such as a phenolic hydroxyl group or an epoxy group. The phenoxy resin may be used alone or in combination of two or more. Specific examples of phenoxy resins include "1256" and "4250" (both of which are phenoxy resins containing a bisphenol A skeleton), "YX8100" (phenoxy resin containing a bisphenol S skeleton), and "YX6954" (phenoxy resin containing a bisphenol acetophenone skeleton) manufactured by Mitsubishi Chemical Corporation. Other examples include "FX280" and "FX293" manufactured by Nippon Steel & Sumikin Chemical Co., Ltd., and "YL7500BH30", "YX6954BH30", "YX7553", "YX7553BH30", "YL7769BH30", "YL6794", "YL7213", "YL7290", and "YL7482" manufactured by Mitsubishi Chemical Corporation.

[0099] Examples of polyvinyl acetal resin include polyvinyl formal resin and polyvinyl butyral resin, and polyvinyl butyral resin is preferred.Specific examples of polyvinyl acetal resin include "Denka Butyral 4000-2", "Denka Butyral 5000-A", "Denka Butyral 6000-C", and "Denka Butyral 6000-EP" manufactured by Denki Kagaku Kogyo Co., Ltd., and S-LEC BH series, BX series (e.g. BX-5Z), KS series (e.g. KS-1), BL series, and BM series manufactured by Sekisui Chemical Co., Ltd.

[0100] Specific examples of polyimide resins include "Rikacoat SN20" and "Rikacoat PN20" manufactured by New Japan Chemical Co., Ltd. Specific examples of polyimide resins also include modified polyimides such as linear polyimides obtained by reacting bifunctional hydroxyl-terminated polybutadiene, a diisocyanate compound, and a tetrabasic acid anhydride (polyimides described in JP-A-2006-37083), and polysiloxane skeleton-containing polyimides (polyimides described in JP-A-2002-12667 and JP-A-2000-319386, etc.).

[0101] Specific examples of polyamide-imide resins include "Viromax HR11NN" and "Viromax HR16NN" manufactured by Toyobo Co., Ltd. Specific examples of polyamide-imide resins also include modified polyamide-imides such as "KS9100" and "KS9300" (polysiloxane skeleton-containing polyamide-imide) manufactured by Hitachi Chemical Co., Ltd.

[0102] A specific example of the polyethersulfone resin is "PES5003P" manufactured by Sumitomo Chemical Co., Ltd. A specific example of the polyphenylene ether resin is "OPE-2St 1200" oligophenylene ether-styrene resin manufactured by Mitsubishi Gas Chemical Co., Ltd.

[0103] Specific examples of polysulfone resins include polysulfones "P1700" and "P3500" manufactured by Solvay Advanced Polymers.

[0104] Among them, the (G) thermoplastic resin is preferably a phenoxy resin or a polyvinyl acetal resin. Therefore, in a preferred embodiment, the thermoplastic resin includes at least one selected from the group consisting of a phenoxy resin and a polyvinyl acetal resin. Among them, the thermoplastic resin is preferably a phenoxy resin, and more preferably a phenoxy resin having a weight average molecular weight of 40,000 or more.

[0105] When the resin composition contains the (G) thermoplastic resin, the content of the (G) thermoplastic resin is preferably 0.1% by mass or more, more preferably 0.2% by mass or more, and even more preferably 0.3% by mass or more, based on 100% by mass of the non-volatile components in the resin composition. The upper limit is preferably 5% by mass or less, more preferably 3% by mass or less, and even more preferably 1% by mass or less. By keeping the content of the (G) thermoplastic resin within this range, even if an inorganic filler with a small average particle size is used, a cured product having excellent adhesion after the HAST test can be obtained.

[0106] <(H) Optional Additives> In one embodiment, the resin composition may further contain other additives as necessary. Examples of such other additives include flame retardants, organic fillers, organometallic compounds such as organocopper compounds, organozinc compounds, and organocobalt compounds, as well as resin additives such as thickeners, defoamers, leveling agents, adhesion promoters, and colorants.

[0107] Examples of the flame retardant include phosphazene compounds, organic phosphorus flame retardants, organic nitrogen-containing phosphorus compounds, nitrogen compounds, silicone flame retardants, metal hydroxides, etc. Specific examples of the phosphazene compounds include "SPH-100", "SPS-100", "SPB-100", and "SPE-100" manufactured by Otsuka Chemical Co., Ltd., and "FP-100", "FP-110", "FP-300", and "FP-400" manufactured by Fushimi Pharmaceutical Co., Ltd. As flame retardants other than the phosphazene compounds, commercially available products may be used, such as "HCA-HQ" manufactured by Sankosha Co., Ltd. and "PX-200" manufactured by Daihachi Chemical Industry Co., Ltd.

[0108] As the organic filler, any organic filler that can be used when forming an insulating layer of a printed wiring board may be used, such as rubber particles, polyamide fine particles, silicone particles, etc. As the rubber particles, commercially available products may be used, such as "EXL2655" manufactured by Dow Chemical Japan, "AC3401N" and "AC3816N" manufactured by Aica Kogyo Co., Ltd.

[0109] <Physical properties and applications of resin compositions> A cured product obtained by thermally curing a resin composition at 100°C for 30 minutes, 170°C for 30 minutes, and then at 200°C for 90 minutes usually exhibits excellent copper foil peel strength (peel strength) before the HAST test. That is, an insulating layer having excellent adhesion before the HAST test is obtained. The peel strength before the HAST test is preferably 0.4 kgf / cm or more, more preferably 0.5 kgf / cm or more, and even more preferably 0.6 kgf / cm or more. The upper limit is not particularly limited, but may be 10 kgf / cm or less. The copper foil peel strength before the HAST test can be measured by the method described in the examples below.

[0110] The resin composition is thermally cured at 100°C for 30 minutes, 170°C for 30 minutes, and then at 200°C for 90 minutes to obtain a cured product that usually exhibits excellent copper foil peel strength (peel strength) after the HAST test. That is, it provides an insulating layer that has excellent adhesion after the HAST test and can exhibit high adhesion for a long period of time. The peel strength after the HAST test is preferably 0.15 kgf / cm or more, more preferably 0.2 kgf / cm or more, and even more preferably 0.3 kgf / cm or more. The upper limit is not particularly limited, but may be 10 kgf / cm or less. The peel strength after the HAST test can be measured by the method described in the examples below.

[0111] A cured product obtained by thermally curing a resin composition at 100°C for 30 minutes and then at 170°C for 30 minutes usually exhibits excellent smear removability. That is, even if a via hole is formed in the cured product, an insulating layer having a maximum smear length at the bottom of the via hole of 5 μm or less is obtained. The smear removability can be measured by the method described in the examples below.

[0112] The resin composition of the present invention exhibits the characteristic of having a low minimum melt viscosity at 60 to 200°C. That is, it provides a resin composition with excellent wiring embedding properties. The minimum melt viscosity of the resin composition at 60 to 200°C is preferably 5000 poise or less, more preferably 4500 poise or less, and even more preferably 4000 poise or less. The lower limit of the minimum melt viscosity is preferably 100 poise or more, more preferably 1000 poise or more, from the viewpoint of stably maintaining the thickness even if the resin composition layer is thin. The minimum melt viscosity can be measured by a dynamic viscoelasticity method, for example, according to the method described in the examples described later.

[0113] The resin composition of the present invention can provide an insulating layer that has excellent thin-film insulation properties and can maintain adhesion with a conductor layer after a HAST test. Therefore, the resin composition of the present invention can be suitably used as a resin composition for forming an insulating layer of a printed wiring board (resin composition for insulating layer of a printed wiring board), and can be more suitably used as a resin composition for forming an interlayer insulating layer of a printed wiring board (resin composition for interlayer insulating layer of a printed wiring board). In addition, the resin composition of the present invention can be suitably used when the printed wiring board is a circuit board with built-in components, since it provides an insulating layer with good component embedding properties.

[0114] [Resin sheet] The resin sheet of the present invention includes a support and a resin composition layer formed from the resin composition of the present invention provided on the support.

[0115] The thickness of the resin composition layer is preferably 25 μm or less, more preferably 20 μm or less, and even more preferably 15 μm or less, or 10 μm or less, from the viewpoint of making the printed wiring board thinner and being able to provide a cured product with excellent insulation even if it is a thin film. The lower limit of the thickness of the resin composition layer is not particularly limited, but can usually be 1 μm or more, 1.5 μm or more, 2 μm or more, etc.

[0116] Examples of the support include films made of plastic materials, metal foils, and release papers, with films made of plastic materials and metal foils being preferred.

[0117] When a film made of a plastic material is used as the support, examples of the plastic material include polyesters such as polyethylene terephthalate (hereinafter sometimes abbreviated as "PET") and polyethylene naphthalate (hereinafter sometimes abbreviated as "PEN"), polycarbonate (hereinafter sometimes abbreviated as "PC"), acrylics such as polymethyl methacrylate (PMMA), cyclic polyolefins, triacetyl cellulose (TAC), polyether sulfide (PES), polyether ketone, polyimide, etc. Among these, polyethylene terephthalate and polyethylene naphthalate are preferred, and inexpensive polyethylene terephthalate is particularly preferred.

[0118] When a metal foil is used as the support, examples of the metal foil include copper foil, aluminum foil, etc., and copper foil is preferred. As the copper foil, a foil made of a single metal, copper, or an alloy of copper and another metal (e.g., tin, chromium, silver, magnesium, nickel, zirconium, silicon, titanium, etc.) may be used.

[0119] The surface of the support to be bonded to the resin composition layer may be subjected to a matte treatment, a corona treatment, or an antistatic treatment.

[0120] In addition, as the support, a support with a release layer having a release layer on the surface to be bonded to the resin composition layer may be used. The release agent used in the release layer of the support with a release layer may be, for example, one or more release agents selected from the group consisting of alkyd resins, polyolefin resins, urethane resins, and silicone resins. The support with a release layer may be a commercially available product, for example, "SK-1", "AL-5", and "AL-7" manufactured by Lintec Corporation, "Lumirror T60" manufactured by Toray Industries, Inc., "Purex" manufactured by Teijin Limited, and "Unipeel" manufactured by Unitika Limited, which are PET films having a release layer mainly composed of an alkyd resin-based release agent.

[0121] The thickness of the support is not particularly limited, but is preferably in the range of 5 μm to 75 μm, and more preferably in the range of 10 μm to 60 μm. When a support with a release layer is used, it is preferable that the total thickness of the support with a release layer is in the above range.

[0122] In one embodiment, the resin sheet may further include other layers as necessary. Examples of such other layers include a protective film equivalent to the support provided on the surface of the resin composition layer that is not bonded to the support (i.e., the surface opposite to the support). The thickness of the protective film is not particularly limited, but is, for example, 1 μm to 40 μm. By laminating the protective film, adhesion of dirt and the like to the surface of the resin composition layer and scratches can be suppressed.

[0123] The resin sheet can be produced, for example, by preparing a resin varnish by dissolving a resin composition in an organic solvent, applying this resin varnish onto a support using a die coater or the like, and then drying the same to form a resin composition layer.

[0124] Examples of organic solvents include ketones such as acetone, methyl ethyl ketone (MEK), and cyclohexanone; acetates such as ethyl acetate, butyl acetate, cellosolve acetate, propylene glycol monomethyl ether acetate, and carbitol acetate; carbitols such as cellosolve and butyl carbitol; aromatic hydrocarbons such as toluene and xylene; and amide solvents such as dimethylformamide, dimethylacetamide (DMAc), and N-methylpyrrolidone. The organic solvents may be used alone or in combination of two or more.

[0125] Drying may be performed by a known method such as heating or hot air blowing. Drying conditions are not particularly limited, but drying is performed so that the content of organic solvent in the resin composition layer becomes 10 mass % or less, preferably 5 mass % or less. Although it varies depending on the boiling point of the organic solvent in the resin varnish, for example, when a resin varnish containing 30 mass % to 60 mass % of organic solvent is used, the resin composition layer can be formed by drying at 50°C to 150°C for 3 minutes to 10 minutes.

[0126] The resin sheet can be stored in a rolled state. When the resin sheet has a protective film, it can be used by peeling off the protective film.

[0127] [Printed wiring board] The printed wiring board of the present invention includes an insulating layer formed from a cured product of the resin composition of the present invention, a first conductor layer, and a second conductor layer. The insulating layer is provided between the first conductor layer and the second conductor layer, and insulates the first conductor layer from the second conductor layer (the conductor layer may be referred to as a wiring layer).

[0128] The insulating layer is formed by a cured product of the resin composition of the present invention. The thickness of the insulating layer between the first and second conductor layers is preferably 6 μm or less, more preferably 5.5 μm or less, and even more preferably 5 μm or less. The lower limit is not particularly limited, but may be 0.1 μm or more. The distance between the first conductor layer and the second conductor layer (the thickness of the insulating layer between the first and second conductor layers) refers to the thickness t1 of the insulating layer 3 between the main surface 11 of the first conductor layer 1 and the main surface 21 of the second conductor layer 2, as shown in FIG. 1 as an example. The first and second conductor layers are adjacent conductor layers with an insulating layer interposed therebetween, and the main surface 11 and the main surface 21 face each other.

[0129] The thickness t2 of the entire insulating layer is preferably 15 μm or less, more preferably 13 μm or less, and further preferably 10 μm or less. There is no particular lower limit, but it can usually be 1 μm or more, 1.5 μm or more, 2 μm or more, etc.

[0130] The printed wiring board can be produced by using the above-mentioned resin sheet by a method including the following steps (I) and (II). (I) A step of laminating a resin sheet on an inner layer substrate so that a resin composition layer of the resin sheet is bonded to the inner layer substrate. (II) A step of thermally curing the resin composition layer to form an insulating layer

[0131] The "inner layer substrate" used in step (I) is a member that becomes the substrate of a printed wiring board, and examples thereof include a glass epoxy substrate, a metal substrate, a polyester substrate, a polyimide substrate, a BT resin substrate, and a thermosetting polyphenylene ether substrate. The substrate may have a conductor layer on one or both sides, and the conductor layer may be patterned. An inner layer substrate having a conductor layer (circuit) formed on one or both sides of the substrate may be called an "inner layer circuit substrate". In addition, an intermediate product on which an insulating layer and / or a conductor layer is to be further formed during the manufacture of a printed wiring board is also included in the "inner layer substrate" of the present invention. When the printed wiring board is a circuit board with built-in components, an inner layer substrate with built-in components may be used.

[0132] The lamination of the inner layer substrate and the resin sheet can be carried out, for example, by thermocompression bonding the resin sheet to the inner layer substrate from the support side. Examples of the member for thermocompression bonding the resin sheet to the inner layer substrate (hereinafter also referred to as the "thermocompression bonding member") include a heated metal plate (such as a SUS plate) or a metal roll (SUS roll). It is preferable to press the thermocompression member not directly onto the resin sheet, but via an elastic material such as heat-resistant rubber so that the resin sheet can sufficiently follow the surface irregularities of the inner layer substrate.

[0133] The lamination of the inner layer substrate and the resin sheet may be performed by a vacuum lamination method. In the vacuum lamination method, the thermocompression temperature is preferably in the range of 60°C to 160°C, more preferably in the range of 80°C to 140°C, the thermocompression pressure is preferably in the range of 0.098MPa to 1.77MPa, more preferably in the range of 0.29MPa to 1.47MPa, and the thermocompression time is preferably in the range of 20 seconds to 400 seconds, more preferably in the range of 30 seconds to 300 seconds. The lamination is preferably performed under reduced pressure conditions of 26.7hPa or less.

[0134] The lamination can be performed by a commercially available vacuum laminator, such as a vacuum pressure laminator manufactured by Meiki Seisakusho Co., Ltd., a vacuum applicator manufactured by Nikko Materials Co., Ltd., or a batch type vacuum pressure laminator.

[0135] After lamination, the laminated resin sheet may be smoothed under normal pressure (atmospheric pressure), for example, by pressing a thermocompression member from the support side. The pressing conditions for the smoothing treatment may be the same as the thermocompression conditions for the lamination. The smoothing treatment may be performed using a commercially available laminator. The lamination and smoothing treatment may be performed consecutively using the commercially available vacuum laminator.

[0136] The support may be removed between step (I) and step (II) or after step (II).

[0137] In step (II), the resin composition layer is thermally cured to form an insulating layer.

[0138] The conditions for thermally curing the resin composition layer are not particularly limited, and conditions that are usually employed when forming an insulating layer for a printed wiring board may be used.

[0139] For example, the heat curing conditions for the resin composition layer vary depending on the type of resin composition, etc., but the curing temperature is preferably 120° C. to 240° C., more preferably 150° C. to 220° C., and even more preferably 170° C. to 200° C. The curing time is preferably 5 minutes to 120 minutes, more preferably 10 minutes to 100 minutes, and even more preferably 15 minutes to 90 minutes.

[0140] Before the resin composition layer is thermally cured, the resin composition layer may be preheated at a temperature lower than the curing temperature. For example, prior to thermally curing the resin composition layer, the resin composition layer may be preheated at a temperature of 50° C. or more and less than 120° C. (preferably 60° C. or more and 115° C. or less, more preferably 70° C. or more and 110° C. or less) for 5 minutes or more (preferably 5 minutes to 150 minutes, more preferably 15 minutes to 120 minutes, and even more preferably 15 minutes to 100 minutes).

[0141] In manufacturing a printed wiring board, the steps of (III) drilling holes in the insulating layer, (IV) roughening the insulating layer, and (V) forming a conductor layer may be further carried out. These steps (III) to (V) may be carried out according to various methods known to those skilled in the art for use in manufacturing printed wiring boards. When the support is removed after step (II), the support may be removed between step (II) and step (III), between step (III) and step (IV), or between step (IV) and step (V). If necessary, the steps (II) to (V) of forming the insulating layer and the conductor layer may be repeated to form a multilayer wiring board. In this case, the thickness of the insulating layer between each conductor layer (t1 in FIG. 1) is preferably within the above range.

[0142] Step (III) is a step of drilling holes in the insulating layer, which allows holes such as via holes and through holes to be formed in the insulating layer. Step (III) may be performed using, for example, a drill, a laser, plasma, etc., depending on the composition of the resin composition used to form the insulating layer. The dimensions and shape of the holes may be appropriately determined depending on the design of the printed wiring board.

[0143] Step (IV) is a step of roughening the insulating layer. The procedure and conditions of the roughening treatment are not particularly limited, and known procedures and conditions that are usually used when forming an insulating layer of a printed wiring board can be adopted. For example, the insulating layer can be roughened by performing a swelling treatment with a swelling liquid, a roughening treatment with an oxidizing agent, and a neutralization treatment with a neutralizing liquid in this order. The swelling liquid used for the roughening treatment is not particularly limited, but includes an alkaline solution, a surfactant solution, and the like, and is preferably an alkaline solution, and as the alkaline solution, a sodium hydroxide solution and a potassium hydroxide solution are more preferable. Examples of commercially available swelling liquids include "Swelling Dip Securigans P" and "Swelling Dip Securigans SBU" manufactured by Atotech Japan. The swelling treatment with a swelling liquid is not particularly limited, but can be performed, for example, by immersing the insulating layer in a swelling liquid at 30°C to 90°C for 1 minute to 20 minutes. From the viewpoint of suppressing the swelling of the resin of the insulating layer to an appropriate level, it is preferable to immerse the insulating layer in a swelling liquid at 40°C to 80°C for 5 to 15 minutes. The oxidizing agent used in the roughening treatment is not particularly limited, but for example, an alkaline permanganate solution in which potassium permanganate or sodium permanganate is dissolved in an aqueous solution of sodium hydroxide can be mentioned. The roughening treatment using an oxidizing agent such as an alkaline permanganate solution is preferably performed by immersing the insulating layer in an oxidizing agent solution heated to 60°C to 80°C for 10 to 30 minutes. In addition, the concentration of the permanganate in the alkaline permanganate solution is preferably 5% by mass to 10% by mass. Examples of commercially available oxidizing agents include alkaline permanganate solutions such as "Concentrate Compact CP" and "Dosing Solution Securigans P" manufactured by Atotech Japan. The neutralizing solution used in the roughening treatment is preferably an acidic aqueous solution, and a commercially available product is, for example, "Reduction Solution Securigant P" manufactured by Atotech Japan. Treatment with a neutralizing solution can be performed by immersing the surface that has been roughened with an oxidizing agent in a neutralizing solution at 30°C to 80°C for 5 to 30 minutes. From the viewpoint of workability, etc., a method in which the object that has been roughened with an oxidizing agent is immersed in a neutralizing solution at 40°C to 70°C for 5 to 20 minutes is preferred.

[0144] In one embodiment, the arithmetic mean roughness (Ra) of the insulating layer surface after the roughening treatment is preferably 400 nm or less, more preferably 350 nm or less, and even more preferably 300 nm or less. The lower limit is not particularly limited, but it may be preferably 0.5 nm or more, more preferably 1 nm or more, etc. In addition, the root mean square roughness (Rq) of the insulating layer surface after the roughening treatment is preferably 400 nm or less, more preferably 350 nm or less, and even more preferably 300 nm or less. The lower limit is not particularly limited, but it may be preferably 0.5 nm or more, more preferably 1 nm or more, etc. The arithmetic mean roughness (Ra) and root mean square roughness (Rq) of the insulating layer surface can be measured using a non-contact surface roughness meter.

[0145] Step (V) is a step of forming a conductor layer. When no conductor layer is formed on the inner layer substrate, step (V) is a step of forming a first conductor layer, and when a conductor layer is formed on the inner layer substrate, the conductor layer is the first conductor layer and step (V) is a step of forming a second conductor layer.

[0146] The conductor material used for the conductor layer is not particularly limited. In a preferred embodiment, the conductor layer contains one or more metals selected from the group consisting of gold, platinum, palladium, silver, copper, aluminum, cobalt, chromium, zinc, nickel, titanium, tungsten, iron, tin and indium. The conductor layer may be a single metal layer or an alloy layer, and examples of the alloy layer include layers formed from alloys of two or more metals selected from the above group (e.g., nickel-chromium alloy, copper-nickel alloy and copper-titanium alloy). Among them, from the viewpoints of versatility, cost, ease of patterning, etc. of the conductor layer formation, a single metal layer of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver or copper, or an alloy layer of a nickel-chromium alloy, a copper-nickel alloy or a copper-titanium alloy is preferred, a single metal layer of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver or copper, or an alloy layer of a nickel-chromium alloy is more preferred, and a single metal layer of copper is even more preferred.

[0147] The conductor layer may be a single-layer structure or a multi-layer structure in which two or more single metal layers or alloy layers made of different kinds of metals or alloys are laminated. When the conductor layer has a multi-layer structure, the layer in contact with the insulating layer is preferably a single metal layer of chromium, zinc or titanium, or an alloy layer of a nickel-chromium alloy.

[0148] The thickness of the conductor layer depends on the desired design of the printed wiring board, but is generally 3 μm to 35 μm, and preferably 5 μm to 30 μm.

[0149] In one embodiment, the conductor layer may be formed by plating. For example, a conductor layer having a desired wiring pattern can be formed by plating the surface of the insulating layer by a conventionally known technique such as a semi-additive method or a full-additive method, and from the viewpoint of ease of production, it is preferable to form the conductor layer by the semi-additive method. An example of forming the conductor layer by the semi-additive method will be described below.

[0150] First, a plating seed layer is formed on the surface of an insulating layer by electroless plating. Next, a mask pattern is formed on the formed plating seed layer to expose a part of the plating seed layer corresponding to a desired wiring pattern. After a metal layer is formed on the exposed plating seed layer by electrolytic plating, the mask pattern is removed. Thereafter, unnecessary plating seed layer is removed by etching or the like to form a conductor layer having a desired wiring pattern.

[0151] The resin sheet of the present invention provides an insulating layer with good component embedding properties, and can therefore be suitably used when the printed wiring board is a circuit board with built-in components. The circuit board with built-in components can be produced by a known production method.

[0152] A printed wiring board produced using the resin sheet of the present invention may be in an embodiment including an insulating layer that is a cured product of the resin composition layer of the resin sheet, and an embedded wiring layer embedded in the insulating layer.

[0153] [Semiconductor Devices] The semiconductor device of the present invention includes the printed wiring board of the present invention. The semiconductor device of the present invention can be manufactured by using the printed wiring board of the present invention.

[0154] Examples of the semiconductor device include various semiconductor devices used in electric appliances (for example, computers, mobile phones, digital cameras, and televisions) and vehicles (for example, motorcycles, automobiles, trains, ships, and aircraft).

[0155] The semiconductor device of the present invention can be manufactured by mounting a component (semiconductor chip) on a conductive portion of a printed wiring board. The "conductive portion" refers to a portion of a printed wiring board that transmits an electric signal, and the portion may be either on the surface or embedded. The semiconductor chip is not particularly limited as long as it is an electric circuit element made of semiconductor material.

[0156] The method of mounting a semiconductor chip when manufacturing a semiconductor device is not particularly limited as long as the semiconductor chip functions effectively, but specific examples include a wire bonding mounting method, a flip chip mounting method, a bumpless buildup layer (BBUL) mounting method, an anisotropic conductive film (ACF) mounting method, a non-conductive film (NCF) mounting method, etc. Here, the "bumpless buildup layer (BBUL) mounting method" refers to "a mounting method in which a semiconductor chip is directly embedded in a recess in a printed wiring board and the semiconductor chip is connected to the wiring on the printed wiring board." EXAMPLES

[0157] The present invention will be specifically described below with reference to examples. The present invention is not limited to these examples. In the following, "parts" and "%" representing amounts mean "parts by mass" and "% by mass", respectively, unless otherwise specified.

[0158] [Example 1] 10 parts of a bisphenol type epoxy resin ("ZX1059" manufactured by Nippon Steel & Sumitomo Metal Chemical Co., Ltd., a 1:1 mixture of bisphenol A type and bisphenol F type, epoxy equivalent 169) and 50 parts of a naphthol type epoxy resin ("ESN475V" manufactured by Nippon Steel & Sumitomo Metal Chemical Co., Ltd., epoxy equivalent approximately 330) were heated and dissolved in 40 parts of solvent naphtha with stirring. This was cooled to room temperature to prepare an epoxy resin solution composition (A).

[0159] The epoxy resin (A) solution composition was mixed with 5 parts of a phenoxy resin ("YX7553BH30" manufactured by Mitsubishi Chemical Corporation, a 1:1 solution of MEK and cyclohexanone with a solid content of 30% by mass), 5 parts of a phenolic curing agent having a triazine skeleton and a novolak structure ("LA-3018-50P" manufactured by DIC Corporation, active group equivalent of about 151, 2-methoxypropanol solution with a solid content of 50% by mass), 50 parts of an active ester curing agent ("HPC-8000-65T" manufactured by DIC Corporation, active group equivalent of about 223, toluene solution with a solid content of 65% by mass), and a curing accelerator (1-benzyl-2-phenylene sulfide). A resin varnish was prepared by mixing 5 parts of nylimidazole (1B2PZ, MEK solution with 10% solids by mass), 250 parts of spherical silica (average particle size 0.77 μm, Admatechs' SO-C2) surface-treated with an amine-based alkoxysilane compound (Shin-Etsu Chemical's KBM573), and 25 parts of a 40% by mass toluene solution of a maleimide compound (Designer Molecules' BMI3000J, an N-alkyl bismaleimide having a skeleton derived from dimer diamine, formula (6) above). The mixture was uniformly dispersed using a high-speed rotating mixer.

[0160] A polyethylene terephthalate film with a release layer ("AL5" manufactured by Lintec Corporation, thickness 38 μm) was prepared as a support. The resin varnish was uniformly applied onto the release layer of this support so that the thickness of the resin composition layer after drying would be 25 μm. The resin varnish was then dried at 80°C to 120°C (average 100°C) for 4 minutes to obtain a resin sheet including a support and a resin composition layer.

[0161] [Example 2] In Example 1, 25 parts of a 40% by mass toluene solution of a maleimide compound ("BMI3000J" manufactured by Designer Molecules, Inc.) was changed to 25 parts of a 40% by mass toluene solution of a maleimide compound ("BMI1700" manufactured by Designer Molecules, Inc.). A resin varnish and a resin sheet were produced in the same manner as in Example 1, except for the above.

[0162] [Example 3] In Example 1, 25 parts of a 40% by mass toluene solution of a maleimide compound ("BMI3000J" manufactured by Designer Molecules, Inc.) was changed to 25 parts of a 40% by mass toluene solution of a maleimide compound ("BMI1500" manufactured by Designer Molecules, Inc.). A resin varnish and a resin sheet were produced in the same manner as in Example 1, except for the above.

[0163] [Example 4] In Example 1, 25 parts of a 40% by mass toluene solution of a maleimide compound ("BMI3000J" manufactured by Designer Molecules) was changed to 25 parts of a 40% by mass toluene solution of a maleimide compound ("BMI689" manufactured by Designer Molecules, an N-alkyl bismaleimide having a skeleton derived from dimer diamine, the above formula (7)). A resin varnish and a resin sheet were produced in the same manner as in Example 1, except for the above.

[0164] [Comparative Example 1] In Example 1, 25 parts of a 40% by mass toluene solution of a maleimide compound ("BMI3000J" manufactured by Designer Molecules) was changed to 25 parts of a 40% by mass MEK solution of a maleimide compound represented by the following structural formula ("BMI70" manufactured by K.I. Chemicals Co., Ltd.) In addition to the above, a resin varnish and a resin sheet were produced in the same manner as in Example 1. [ka] In the formula, Me represents a methyl group, and Et represents an ethyl group.

[0165] [Comparative Example 2] In Example 2, the amount of spherical silica (average particle size 0.77 μm, Admatechs' "SO-C2") surface-treated with an amine-based alkoxysilane compound (Shin-Etsu Chemical's "KBM573") was changed from 250 parts to 240 parts, and no maleimide compound (Designer Molecules' "BMI3000J") was used. A resin varnish and a resin sheet were produced in the same manner as in Example 2, except for the above.

[0166] [Evaluation method] The resin sheets obtained in the above-mentioned Examples and Comparative Examples were evaluated by the following methods.

[0167] [Method of measuring peel strength] <Preparation of substrate for adhesion evaluation> (1) Surface preparation for interior boards: A glass cloth-based epoxy resin double-sided copper-clad laminate (copper foil thickness 18 μm, substrate thickness 0.8 mm, Panasonic "R1515A") with copper foil on the surface was prepared as an inner layer substrate. The copper foil on the surface of this inner layer substrate was completely removed by etching. It was then dried at 190°C for 30 minutes.

[0168] (2) Lamination of resin sheets: The resin sheets obtained in the above-mentioned Examples and Comparative Examples were laminated on both sides of the inner layer substrate using a batch-type vacuum pressure laminator (a two-stage build-up laminator "CVP700" manufactured by Nikko Materials Co., Ltd.) so that the resin composition layer was bonded to the inner layer substrate. This lamination was performed by reducing the pressure for 30 seconds to 13 hPa or less, and then pressing at a temperature of 100°C and a pressure of 0.74 MPa for 30 seconds.

[0169] The laminated resin sheet was then heat-pressed at atmospheric pressure at 100°C and a pressure of 0.5 MPa for 60 seconds to smooth the surface. The support was then peeled off to obtain an "intermediate laminate I" including the resin composition layer, the inner layer substrate, and the resin composition layer in this order.

[0170] On the other hand, a copper foil having a glossy surface (thickness: 35 μm, "3EC-III" manufactured by Mitsui Mining & Smelting Co., Ltd.) was prepared. The glossy surface of this copper foil was etched with a micro-etching agent ("CZ8101" manufactured by Meck) at a copper etching amount of 1 μm to perform a roughening treatment. The copper foil thus obtained is referred to as "roughened copper foil".

[0171] This roughened copper foil was laminated on both sides of the intermediate multilayer body I such that the surface of the roughened copper foil that had been subjected to the roughening treatment was joined to the resin composition layer of the intermediate multilayer body I. This lamination was performed under the same conditions as the lamination of the resin sheet to the inner layer substrate described above. Thereby, an "intermediate multilayer body II" including a roughened copper foil, a resin composition layer, an inner layer substrate, a resin composition layer, and a roughened copper foil in this order was obtained.

[0172] This intermediate multilayer body II was put into an oven at 100 °C and heated for 30 minutes, and then transferred to an oven at 170 °C and heated for 30 minutes. Next, after taking out the intermediate multilayer body II from the oven to a room temperature atmosphere, it was further put into an oven at 200 °C and additionally heated for 90 minutes. Thereby, thermosetting of the resin composition layer was performed, and an "evaluation substrate A" including a roughened copper foil, an insulating layer as a cured product of the resin composition layer, an inner layer substrate, an insulating layer as a cured product of the resin composition layer, and a roughened copper foil in this order was obtained. In this evaluation substrate A, the roughened copper foil corresponds to the conductor layer.

[0173] <Measurement of peel strength before HAST test> Using the above-described evaluation substrate A, the peel strength between the roughened copper foil and the insulating layer was measured. This measurement of the peel strength was performed in accordance with JIS C6481. Specifically, the peel strength was measured by the following operation.

[0174] An incision was made in the roughened copper foil of the evaluation substrate A to surround a rectangular portion with a width of 10 mm and a length of 100 mm. One end of this rectangular portion was peeled off and grasped with a gripping tool (manufactured by T.S.E. Co., Ltd., auto-comb type testing machine "AC-50C-SL"). The range of 35 mm in length of the rectangular portion was peeled off vertically, and the load (kgf / cm) at the time of this peeling was measured as the peel strength. The above-mentioned peeling was performed at room temperature at a speed of 50 mm / min.

[0175] <Measurement of Peel Strength after HAST Test> Thereafter, the evaluation substrate A was subjected to a HAST test in an environment of a temperature of 130 °C and a humidity of 85% RH for 100 hours. After this HAST test, the peel strength between the roughened copper foil and the insulating layer of the evaluation substrate A was measured by the same method as before the HAST test.

[0176] [Evaluation of Smear Removal Property] (1) Substrate Treatment of Interior Substrate: As an inner layer substrate, a glass cloth base epoxy resin double-sided copper-clad laminate having a copper foil on the surface (copper foil thickness: 18 μm, substrate thickness: 0.8 mm, "R1515A" manufactured by Panasonic Corporation) was prepared. The copper foil on the surface of this inner layer substrate was etched with a micro-etching agent ("CZ8101" manufactured by Meck Co., Ltd.) with a copper etching amount of 1 μm to perform a roughening treatment. Thereafter, drying was performed at 190 °C for 30 minutes.

[0177] (2) Lamination and Curing of Resin Sheet: The resin sheets obtained in the above-described examples and comparative examples were laminated on both sides of the inner layer substrate using a batch type vacuum pressure laminator (two-stage build-up laminator "CVP700" manufactured by Nichco Materials Co., Ltd.) so that the resin composition layer was joined to the inner layer substrate. This lamination was performed by reducing the pressure for 30 seconds to make the atmospheric pressure 13 hPa or less and then performing pressure bonding at a temperature of 100 °C and a pressure of 0.74 MPa for 30 seconds. The laminated resin sheet was then heat-pressed at atmospheric pressure at 100°C under a pressure of 0.5 MPa for 60 seconds to smooth it, and then placed in a 100°C oven for 30 minutes and heated, and then transferred to a 170°C oven for 30 minutes.

[0178] (3) Via hole formation: Via Mechanics CO 2 Using a laser processing machine (LK-2K212 / 2C), the insulating layer was processed under the conditions of a frequency of 2000 Hz, a pulse width of 3 μs, an output of 0.95 W, and a shot number of 3, to form via holes with a top diameter of 50 μm on the insulating layer surface and a diameter of 50 μm on the insulating layer bottom surface. After that, the support was peeled off to obtain a circuit board.

[0179] (4) Roughening treatment The insulating layer surface of the circuit board was immersed in a swelling liquid, Swelling Dip Securigant P, manufactured by Atotech Japan, at 60°C for 10 minutes. Next, the insulating layer surface of the circuit board was immersed in a roughening liquid, Concentrate Compact P (KMnO 4 The circuit board was immersed in a neutralizing solution (NaOH: 60 g / L, NaOH: 40 g / L) at 80° C. for 25 minutes. Finally, the insulating layer surface of the circuit board was immersed in a neutralizing solution, Reduction Solution Securigant P, manufactured by Atotech Japan, at 40° C. for 5 minutes.

[0180] (5) Evaluation of residue at the bottom of via holes The periphery of the bottom of the via hole was observed with a scanning electron microscope (SEM), and the maximum smear length from the wall surface of the bottom of the via hole was measured from the obtained image and evaluated according to the following criteria. ○: Maximum smear length is less than 5 μm ×: Maximum smear length is 5 μm or more

[0181] [Measurement of minimum melt viscosity] The melt viscosity of the resin composition layer in the resin sheet produced in the examples and comparative examples was measured using a dynamic viscoelasticity measuring device (UBM's "Rheosol-G3000"). This measurement was performed on a 1 g sample taken from the resin composition layer using parallel plates with a diameter of 18 mm. The measurement conditions were as follows: starting temperature 60°C to 200°C, heating rate 5°C / min, measurement temperature interval 2.5°C, and vibration 1 Hz / deg. The minimum melt viscosity was calculated from the measured melt viscosity values ​​obtained.

[0182] [result] The results of the above-mentioned Examples and Comparative Examples are shown in the following table. In the following table, the amount of each component is expressed as the amount of non-volatile components. In the following table, the meanings of the abbreviations are as follows. ESN475V: Naphthol type epoxy resin, manufactured by Nippon Steel & Sumikin Chemical Co., Ltd., epoxy equivalent: approx. 330 ZX1059: Bisphenol type epoxy resin, manufactured by Nippon Steel & Sumikin Chemical Co., Ltd., 1:1 mixture of bisphenol A type and bisphenol F type, epoxy equivalent 169 BMI3000J: Maleimide compound, manufactured by Designer Molecules BMI1700: Maleimide compound, Designer Molecules BMI1500: Maleimide compound, Designer Molecules BMI689: Maleimide compound, Designer Molecules BMI70: Maleimide compound, manufactured by K.I. Chemicals HPC-8000-65T: Active ester curing agent, manufactured by DIC, active group equivalent weight approx. 223, solid content 65% by mass in toluene solution SO-C2: Spherical silica surface-treated with an amine-based alkoxysilane compound ("KBM573" manufactured by Shin-Etsu Chemical Co., Ltd.), average particle size 0.5 μm, manufactured by Admatechs Co., Ltd. LA-3018-50P: Phenolic hardener with triazine skeleton and novolac structure, manufactured by DIC, active group equivalent weight approx. 151, 2-methoxypropanol solution with 50% solids YX7553BH30: Phenoxy resin, manufactured by Mitsubishi Chemical Corporation, 1:1 solution of MEK and cyclohexanone with a solid content of 30% by mass 1B2PZ: Curing accelerator, 1-benzyl-2-phenylimidazole, MEK solution with 10% solids by mass

[0183] [Table 1]

[0184] In Examples 1 to 4, it was confirmed that even when components (C) to (G) were not contained, the results were similar to those of the above Examples, although to a different extent. [Explanation of symbols]

[0185] 1 First Conductor Layer 11: Main surface of first conductor layer 2 Second conductor layer 21 Main surface of second conductor layer 3. Insulation layer t1: Distance between the first and second conductor layers (thickness of the insulating layer between the first and second conductor layers) t2 Total thickness of the insulating layer

Claims

1. A resin composition comprising (A) an epoxy resin, (B) a maleimide compound, (C) an active ester compound, and (G) a thermoplastic resin, The component (B) is a maleimide compound represented by the following general formula (B-4), The content of the component (C) is 3% by mass or more and 30% by mass or less, when the non-volatile components in the resin composition are taken as 100% by mass, A resin composition, wherein the content of the component (G) is 0.1% by mass or more and 5% by mass or less, when the total amount of non-volatile components in the resin composition is 100% by mass. 【Chemistry 1】 In general formula (B-4), R 3 represents an alkylene group having 5 or more carbon atoms which may have a substituent, R 4 represents a divalent group having an aromatic ring which may have a substituent, R 5 each independently represents an alkyl group having 5 or more carbon atoms, n2 is 0, m represents an integer of 1 to 3.

2. A resin composition comprising (A) an epoxy resin, (B) a maleimide compound, and (G) a thermoplastic resin, The component (B) is a maleimide compound represented by the following general formula (B-4), A resin composition having a content of the component (G) of 0.1% by mass or more and 5% by mass or less, when the total amount of non-volatile components in the resin composition is taken as 100% by mass (however, this does not include resin compositions in which the mass ratio of the bismaleimide compound to the allylated bisphenol type epoxy resin (bismaleimide compound / allylated bisphenol type epoxy resin) is in the range of 50 / 50 to 95 / 5). 【Chemistry 2】 In general formula (B-4), R 3 represents an alkylene group having 5 or more carbon atoms which may have a substituent, R 4 represents a divalent group having an aromatic ring which may have a substituent, R 5 each independently represents an alkyl group having 5 or more carbon atoms, n2 is 0, m represents an integer of 1 to 3.

3. A resin composition comprising (A) an epoxy resin, (B) a maleimide compound, (C) an active ester compound, and (G) a thermoplastic resin, The component (B) is a maleimide compound represented by the following general formula (B-2): The content of the (B) component is 0.1% by mass or more and 10% by mass or less, when the total amount of non-volatile components in the resin composition is 100% by mass, The content of the component (C) is 3% by mass or more and 30% by mass or less, when the non-volatile components in the resin composition are taken as 100% by mass, A resin composition, wherein the content of the component (G) is 0.1% by mass or more and 5% by mass or less, when the total amount of non-volatile components in the resin composition is 100% by mass. 【Chemistry 3】 In formula (B-2), R' each independently represents an alkylene group having 5 or more carbon atoms which may have a substituent, A each independently represents an alkylene group having 5 or more carbon atoms which may have a substituent or a divalent group having an aromatic ring which may have a substituent, and n represents an integer of 1 to 10.

4. A resin composition comprising (A) an epoxy resin, (B) a maleimide compound, (C) an active ester compound, and (G) a thermoplastic resin, The component (B) is a maleimide compound represented by the following general formula (B-2): The content of the (B) component is 0.1% by mass or more and 10% by mass or less, when the total amount of non-volatile components in the resin composition is 100% by mass, The content of the component (C) is 3% by mass or more and 30% by mass or less, when the non-volatile components in the resin composition are taken as 100% by mass, A resin composition having a content of the component (G) of 0.1% by mass or more and 5% by mass or less, when the total amount of non-volatile components in the resin composition is taken as 100% by mass (however, this does not include resin compositions in which the mass ratio of the bismaleimide compound to the allylated bisphenol type epoxy resin (bismaleimide compound / allylated bisphenol type epoxy resin) is in the range of 50 / 50 to 95 / 5). 【Chemistry 4】 In formula (B-2), R' each independently represents an alkylene group having 5 or more carbon atoms which may have a substituent, A each independently represents an alkylene group having 5 or more carbon atoms which may have a substituent or a divalent group having an aromatic ring which may have a substituent, and n represents an integer of 1 to 10.

5. The resin composition according to claim 1 or 2, wherein the content of the component (B) is 0.1% by mass or more and 10% by mass or less, based on 100% by mass of non-volatile components in the resin composition.

6. The resin composition according to claim 2 , further comprising (C) an active ester compound.

7. 7. The resin composition according to claim 1, wherein the content of the component (C) is 5% by mass or more, based on 100% by mass of non-volatile components in the resin composition.

8. The resin composition according to any one of claims 1 to 7, further comprising (D) an inorganic filler.

9. The resin composition according to claim 8, wherein the content of the component (D) is 50 mass% or more.

10. In the general formula (B-2), each A independently represents a cyclic alkylene group having 5 or more carbon atoms which may have a substituent; a divalent group having a benzene ring which may have a substituent; a divalent group having a phthalimide ring which may have a substituent; or a divalent group having a pyromellitic diimide ring which may have a substituent. The resin composition according to claim 3 or 4.

11. The resin composition according to claim 3 or 4, wherein in general formula (B-2), at least one A represents a divalent group having a phthalimide ring which may have a substituent, or a divalent group having a pyromellitic diimide ring which may have a substituent.

12. The resin composition according to any one of claims 1 to 11, wherein the component (G) is at least one selected from the group consisting of a phenoxy resin, a polyvinyl acetal resin, a polyimide resin, a polyamideimide resin, a polyethersulfone resin, and a polysulfone resin.

13. The resin composition according to any one of claims 1 to 12, further comprising a curing accelerator (F), the component (F) comprising an imidazole-based curing accelerator.

14. The resin composition according to any one of claims 1 to 13, which is for forming an insulating layer of a printed wiring board.

15. The resin composition according to any one of claims 1 to 14, which is used for forming an interlayer insulating layer of a printed wiring board.

16. A resin sheet comprising a support and a resin composition layer formed from the resin composition according to any one of claims 1 to 15 provided on the support.

17. The resin sheet according to claim 16, wherein the resin composition layer has a thickness of 25 µm or less.

18. A printed wiring board including a first conductor layer, a second conductor layer, and an insulating layer formed between the first conductor layer and the second conductor layer, A printed wiring board, wherein the insulating layer is a cured product of the resin composition according to any one of claims 1 to 15.

19. A semiconductor device comprising the printed wiring board according to claim 18.

Citation Information

Patent Citations

  • Epoxy-based resin composition, prepreg, cured product, sheet-like molded article, laminate plate, and multilayer laminate plate

    JP2010053334A

  • Resin composition

    JP2011256300A

  • Epoxy resin composition

    JP2013234328A

  • Resin composition

    JP2014098148A

  • Resin sheet and printed wiring board

    JP2016010964A